Kajian Eksperimental Penggunaan Pasir Pantai Sebagai Agregat Halus Pada Beton Normal Dengan Penambahan Silica Fume - Triyono, Agus; Suryono, Wiwid; Fatimah, Siti; Winiasri, Linda; Rozi, Fahrur (Universitas Nahdlatul Ulama Blitar, 2025)
This study aims to examine the use of beach sand as an alternative material for fine aggregate in normal concrete of K-225 quality with the addition of silica fume. The method used is an experimental method by testing compressive strength and slump values. In this study, 4 types of test pieces were used, namely concrete mixture using river sand (BN), concrete mixture using beach sand (BPP), concrete mixture using beach sand with the addition of 10% silica fume (BPPSF10), and concrete mixture using beach sand with the addition of silica fume 20% (BPPSF20). Based on the test results, it can be concluded that the concrete mixture using beach sand (BPP, BPPSF10 and BPPSF20) has a lower compressive strength than the concrete mixture using river sand. The addition of silica fume to the beach sand concrete mixture by 10% and 20% can increase the compressive strength of concrete but has not been able to achieve the planned compressive strength. Meanwhile, the slump value in the concrete mixture using beach sand is lower than the slump value of the concrete mixture using river sand.